Pengaruh Belanja Pemerintah Terhadap Pendapatan Perkapita Indonesia - Jamaludin Jamaludin; Hijri Juliansyah (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study was conducted to determine the effect of government spending on the education and health sectors on Indonesia's per capita income. The data used in this study are time series data from 1990- 2018 obtained from the website of the Ministry of Finance of the Republic of Indonesia and the Indonesian Central Bureau of Statistics (BPS). The data are then analyzed using dynamic analysis of the ARDL model. The results showed that government spending in the education sector had no effect on Indonesia's per capita income for the 1990-2018 period, both in the long and short term. Government spending in the health sector affects Indonesia's per capita income for the 1990-2018 period in the short and long term